Optimasi Basis Gel dan Evaluasi Sediaan Gel Anti Jerawat Ekstrak Daun Sirih Hitam (Piper betle L. Var Nigra): Gel Base Optimization and Evaluation of Anti-Acne Gel Black Betel Leaf Extract (Piper betle L. Var Nigra) - Velita Rosari; Nurul Fitriani; Fajar Prasetya (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Gel is a semi-solid preparation that is clear, translucent and contains active ingredients. Acne is a skin disorder caused by the Propionibacterium acnes bacteria. Black betel (Piper betle L. var Nigra) contains alkaloids, flavonoids, saponins, tannins, steroids, triterpenoids, and polyphenolates which function as antibacterial. So that it can be formulated as an active substance in anti-acne gel preparations. The purpose of this study was to obtain a gel base with good physical stability and to evaluate the gel preparations mixed with black betel leaf extract (Piper betle L. var Nigra). Base optimization is done with 4 formulas with variations of Carbopol and TEA, namely B1, B2, B3, and B4. After getting the best gel base, then 3 formulas were made with various concentrations of black betel leaf extract (Piper betle L. var Nigra), namely F1 5%, F2 10%, and F3 15%. Then performed the physical stability test of the anti-acne gel preparation including organoleptic, homogeneity, pH, dispersion, adhesion, syneresis and viscosity for 16 days. The results obtained in the base optimization are clear, smell typical of bases, thick, homogeneous, pH range 6.1-6.8, spreadability 5.8-6.9 cm, adhesion 8-21 seconds, and viscosity 2.75. -5.81 Pa.s. The results obtained on the anti-acne gel are dark green, unique extract odor, thick, homogeneous, no syneresis, pH range 5.6-6.1, spreadability 6.0-6.9 cm, adhesion 14-21. seconds, and a viscosity of 2.12-6.81 Pa.s. The results showed that the gel base formula B4 was in accordance with the standard physical stability parameters. The addition of black betel leaf extract (Piper betle L. var Nigra) to the gel base affected the physical stability of the anti-acne gel preparation, but it was still included in the standard parameters of a good gel.